SOSIALISASI DAN EDUKASI MANAJEMEN UNTUK PENGUATAN KELEMBAGAAN KKSA KABUPATEN KEDIRI - Zulistiani, Zulistiani; Aliami, Sri; Hakimah, Ema Nurzainul; Annisa, Aulia; Paramitha, Dyah Ayu; Aini, Silvi Nur; Kholila, Nova Nor (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2025)
This community service exertion aims to strengthen the institutional structure of the An- Nisa Sharia Consumer Cooperative( KKSA) of Kediri Regency through socialization and operation education to directors and members. The main problems faced by mates are the sour organizational and institutional structure of the collaborative, as well as the lack of understanding of the introductory principles of sharia consumer cooperatives. This exertion was carried out through interactive lectures, group conversations, and simulations of preparing institutional bribes. The results of the exertion showed an increase in actors' understanding of the organizational structure of the collaborative, the division of tasks for directors, and the significance of institutional documents. This program has a positive original impact as a foundation for the metamorphosis of collaborative institutions that are more professional and grounded on sharia values.